Does the Actualization of Cultural Insights in the Accounting Curriculum Contribute to Students' Perceptions of Ethics? - Amaliah, Tri Handayani; Pakaya, Lukman; Noholo, Sahmin; Niswatin, Niswatin; Yusuf, Nilawaty; Mattoasi, Mattoasi; Damity, Fatmawaty (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This study examines the effect of culture-based accounting models on students' perceptions of ethics. This study used an experimental method using a post-test-only group design. Participants in this study were accounting students of Gorontalo State University in two classes of Business Ethics and Accountant Profession courses. The participants were classified into an experimental group (25 students) and a control group (16 students). This research proves that the integrated accounting learning model of cultural insights shapes students' perceptions of ethics. The results showed a significant difference between the perception of experimental group participants and control group participants. This is due to the different treatments given to the experimental group, which include cultural stimuli in the learning process of business ethics and the accountant profession, and not caused by differences between groups before the experiment. The results of this study also show that the influence of the integrated accounting learning process of cultural insights on students' perceptions of ethics is greater than the influence of differences between individuals on students' perceptions of ethics.